2010
DOI: 10.2353/ajpath.2010.090810
|View full text |Cite
|
Sign up to set email alerts
|

Forced Expression of Methionine Adenosyltransferase 1A in Human Hepatoma Cells Suppresses in Vivo Tumorigenicity in Mice

Abstract: Methionine adenosyltransferase (MAT) catalyzes the synthesis of S-adenosylmethionine , the principal methyl donor, and is encoded by MAT1A and MAT2A in mammals. Normal liver expresses MAT1A, which is silenced in hepatocellular carcinoma. We have shown that hepatoma cells overexpressing MAT1A grew slower, but whether this is also true in vivo remains unknown. To investigate the effect of overexpressing MAT1A on in vivo tumorigenesis, we generated stable transfectants of Huh7 cells overexpressing either MAT1A or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 35 publications
3
59
0
Order By: Relevance
“…A better strategy to maintain increased SAMe level in liver cancer cells is to induce the expression of MAT1A. Consistent with this, liver cancer cells with forced expression of MAT1A doubled-cellular SAMe levels grew slower in vitro and in vivo and exhibited reduced angiogenesis, ERK, and AKT activation and increased apoptosis in vivo (12). This proof of concept prompted the current work to investigate whether MAT1A expression is regulated by microRNAs (miRNAs) that are dysregulated in HCC, as miRNAs are potentially much better therapeutic targets.…”
Section: Introductionmentioning
confidence: 58%
“…A better strategy to maintain increased SAMe level in liver cancer cells is to induce the expression of MAT1A. Consistent with this, liver cancer cells with forced expression of MAT1A doubled-cellular SAMe levels grew slower in vitro and in vivo and exhibited reduced angiogenesis, ERK, and AKT activation and increased apoptosis in vivo (12). This proof of concept prompted the current work to investigate whether MAT1A expression is regulated by microRNAs (miRNAs) that are dysregulated in HCC, as miRNAs are potentially much better therapeutic targets.…”
Section: Introductionmentioning
confidence: 58%
“…It has been found that Mat1A:Mat2A switch and low SAM levels, associated with CpG hypermethylation of Mat1A promoter, and prevalent CpG hypomethylation in Mat2A promoter of fast growing HCC (Frau et al, 2012). Forced MAT1A overexpression in HepG2 and Huh7 cells led to rise in SAMe level, decreased cell proliferation, increased apoptosis (Li et al, 2010;Frau et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…CD31, immunohistochemical marker, was used to estimate microvessel proliferation in the tumor [3]. In the present study, we investigated the levels of CD31 following the effect of As 2 O 3 and GRg3 on the inhibiting angiogenesis in hepatic VX2 carcinoma.…”
Section: As 2 O 3 and Grg3 Down-regulated Cd31 And Tumor Angiogenesismentioning
confidence: 99%
“…Meanwhile, various immunohistochemical markers were used to estimate microvessel proliferation in tumors, such as pan-endothelial markers CD31 [3] and antibodies against angiogenic proteins like vascular endothelial growth factor (VEGF) [4]. In this study, we investigated the roles of As 2 O 3 and GRg3 in VX2 carcinoma model of rabbits through CD31 and VEGF.…”
Section: Introductionmentioning
confidence: 99%